COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBYEK WISATA HUTAN BAMBU KEPUTIH DI KOTA SURABAYA - Yusuf Hariyoko (Universitas Tribhuwana Tunggadewi, 2023)
Tourism objects are very important to manage, because they have a good role in the regional economy and society. The Bamboo Forest in Surabaya City is a new tourist attraction that continues to increase in its attractiveness, but there are still many shortcomings. This research was conducted to see that the development that has been carried out by the Surabaya City Government is able to answer the existing problems. This research uses qualitative research with a case study approach. The results show that the development of bamboo forest tourism objects is quite good. Communication has been built between the government and its agencies, as well as the community. The management of human resources has been well regulated and the financial problems of the city government in the development of tourism objects are needed to build supporting facilities. The social and economic environment gives a good signal with the existence of bamboo forests. The community has got a role and needs to increase its participation again. And, there are still problems in the provision of infrastructure and infrastructure in bamboo forest tourism objects.AbstrakObyek wisata sangat penting untuk dikelola, karena punya peran yang bagus dalam perekonomian daerah dan masyarakat. Hutan Bambu di Kota Surabaya adalah obyek wisata baru yang terus meningkat daya tariknya, namun masih banyak kekurangan. Penelitian ini dilakukan untuk melihat pengembangan yang sudah dilakukan oleh Pemerintah Kota Surabaya mampu menjawab permasalahan yang ada. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan studi kasus. Hasil menunjukkan bahwa dalam pengembangan obyek wisata hutan bambu sudah cukup baik. Komunikasi sudah dibangun antara pemerintah dengan instansi-instansinya, beserta masyarakat. Sumber daya manusia pengelola sudah diatur dengan baik dan masalah finansial dari pemerintah kota dalam pengembangan obyek wisata yang diperlukan untuk membangun fasilitas pendukung. Lingkungan sosial dan ekonomi memberikan sinyal yang baik dengan adanya hutan bambu. Masyarakat sudah mendapat peran dan perlu untuk ditingkatkan lagi partisipasinya. Serta, masih adanya permasalahan pada penyediaan infrastruktur dan prasarana yang ada di obyek wisata Hutan Bambu.